Le fonio, une céréale africaine - Cruz, Jean-François (éditions Quae, 2011)
"For years a basic food of many rural African communities, fonio, an African cereal with very small grains, has now been discovered by urban consumers in major African cities. This book describes the plant and grains and provides information on miscellaneous cultivation and production systems in a variety of environments. It describes the principal traditional fonio production and processing techniques and suggests possible areas for improvement. It shows a keen interest in improved promotion of fonio, by touching on such aspects as preparation of new products, marketing and consumption."